Highly Selective Separation of C2H2/CO2 and C2H2/C2H4 in an N-Rich Cage-Based Microporous Metal-Organic Framework - Lingzhi Yang; Wenpeng Xie; Qiuju Fu; Liting Yan; Shuo Zhang; Huimin Jiang; Liangjun Li; Xin Gu; Dandan Liu; Pengcheng Dai; Qingbin Zheng; Xuebo Zhao (Adsorption Science & Technology)
The separation of acetylene (C2H2) from carbon dioxide (CO2) and the purification of ethylene (C2H4) from C2H2 are quite essential processes for the chemical industry. However, these processes are challenging due to their similar physical properties, including molecule sizes and boiling points. Herein, we report an N-rich cage-based microporous metal-organic framework (MOF), [Cd5(Tz)9](NO3) (termed as Cd-TZ, TZ stands for tetrazole), and its highly efficient separation of C2H2/CO2 and C2H2/C2H4. Single-component gas adsorption isotherms reveal that Cd-TZ exhibits high C2H2 adsorption capacity (3.10 mmol g-1 at 298 K and 1 bar). The N-rich cages in Cd-TZ can trap C2H2 with a higher isosteric heat of adsorption (40.8 kJ mol-1) than CO2 and C2H4 owing to the robust host-guest interactions between the noncoordinated N atoms and C2H2, which has been verified by molecular modeling studies. Cd-TZ shows a high IAST selectivity for C2H2/CO2 (8.3) and C2H2/C2H4 (13.3). The breakthrough simulations confirm the potential for separating C2H2/CO2 and the purification of C2H4 from C2H2.